Perancangan Sistem Perparkiran Rendah Biaya Berbasis Ponsel Cerdas Android - Pradana, Adlan Bagus; Jatinugroho, Dwiantono; Abidin, Fakhrurrozi Zainal; Ma’rifadiyah, Cholifah (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2019)
Every public space requires vehicle parking facilities. The registration system was created to ensure the safety of parked vehicles. The existing registration system is done manually by giving a ticket written by the vehicle number by the officer. During exit, ticket is shown to the officer for being matched with the vehicle number. This system has a disadvantage because parking tickets have the opportunity to be counterfeit; the time of verification is dependent on humans and the use of disposable paper. The purpose of this study is to solve problems at low cost. The chosen solution is to register with the QR Code on the driver and vehicle when entering and leaving. This frees the riding-vehicle pair when entering the same as when exiting, because the system will not open the door if the driver-vehicle pair is different between when entering and exiting. The next advantage is reducing human problems. To support this goal, use smart and smart devices that use Android-based smartphones, Google Sheets, Google Forms, MIT App Inventor and TinyDB. This Android-based parking registration system has been proven to increase parking safety levels and reduce waiting times while reducing paper usage.